First measurement of time-dependent CP violation in B0s → K+K− decays - Aaij, Roel; Aquines Gutiérrez, Osvaldo; Bachmann, Sebastian; Bien, Alexander; Blouw, Johan; Britsch, Markward; De Cian, Michel; Di Canto, Angelo; Dordei, Francesca; Färber, Christian; Fontana, Marianna; Gersabeck, Evelina; et al. (Journal of high energy physics, 2013)
Direct and mixing-induced CP-violating asymmetries in $ B_s^0→ {K^{+}}{K^{-}} $decays are measured for the first time using a data sample of pp collisions, corresponding to an integrated luminosity of 1.0 fb−1, collected with the LHCb detector at a centre-of-mass energy of 7 TeV. The results are CKK = 0.14 ± 0.11 ± 0.03 and SKK = 0.30 ± 0.12 ± 0.04, where the first uncertainties are statistical and the second systematic. The corresponding quantities are also determined for B0 → π+π− decays to be Cππ = −0.38 ± 0.15 ± 0.02 and Sππ = −0.71 ± 0.13 ± 0.02, in good agreement with existing measurements.